Weeds as a source for human consumption. A comparison between tropical and temperate Latin America - Martha Díaz-Betancourt; Luciana Ghermandi; Ana Ladio; Ismael R. López-Moreno; Estela Raffaele; Eduardo H. Rapoport (Revista de Biología Tropical, 1999)
Weeds abound in urban and agricultural environments. Depending on region and site, up to 66% of weed species are edible, and may constitute an additional food source for humans. Based on 400 samples, ¼ m² each, collected in tropical areas (e.g., roadsides, urban vacant lots, streets, sugar cane and coffee plantations in Coatepec, Mexico), average figures of edible fresh biomass vary between 1277 and 3582 kg/ha. A similar survey performed in a temperate area (739 samples in Bariloche, Argentina) showed mean values between 287 and 2939 kg/ha. A total of 43 species were sampled in Coatepec and 32 species in Bariloche. The general means were 2.1 and 1.3 tons/ha, respectively. At a greater geographic scale, a comparison between Mexican and Argentine weeds shows that, proportionately, the food parts vary a little between regions. In general, from higher to lower, the order of uses goes from leaves, seeds, roots, fruits, herbals, flowers and condiments. Edible roots (including bulbs and rhizomes) appear to be more common among perennials than among annuals. Las malezas abundan en ambientes urbanos y rurales. Según la región y lugar, hasta el 66% de las especies de malezas pueden ser comestibles y constituir un recurso alimentario adicional para el ser humano. Sobre la base de 400 muestras de ¼ m² cada una, recolectadas en áreas tropicales (rutas, terrenos baldíos, calles y plantaciones en Coatepec, México) el promedio de la biomasa en peso fresco varió entre 1 277 y 3 582 kg/ha. Un muestreo similar en un área templada (739 muestras en Bariloche, Argentina) arrojó valores medios entre 287 y 2 939 kg/ha. En total se registraron 43 especies en Coatepec y 32 especies en Bariloche. La media general (total) fue de 2.1 y 1.3 ton/ha, respectivamente. A una escala geográfica mayor, una comparación entre las malezas mexicanas y argentinas no mostró mayores variaciones regionales en cuanto a qué partes u órganos son los comestibles. En ambos lugares, el orden de aprovechamiento, de mayor a menor, fue: hojas, semillas, raíces, frutos, infusiones, flores y condimentos. Las raíces comestibles (incluyendo bulbos y rizomas) parecen ser más comunes entre las especies perennes que entre las anuales.